Cryptochrome 1 activation inhibits melanogenesis and melanosome transport through negative regulation of cAMP/PKA/CREB signaling pathway - Gao, Rongyin; Zhang, Ximei; Zou, Kun; Meng, Duo; Lv, Jinpeng (Frontiers in Pharmacology, 2023)
Cutaneous pigmentation was recently shown to be an event regulated by clock proteins. Cryptochrome (CRY) is a key protein composing the feedback loop of circadian clock, however, the function of CRY in melanocytes remains unclear. Here, we found that KL001, a synthetic small molecule modulator of CRY1, inhibited melanin synthesis, as well as reduced melanocyte dendrite elongation and melanosome transport. In addition, the dominant role of CRY1 in KL001-induced anti-melanogenesis was revealed by small interfering RNA transfection. Cellular tyrosinase activity and expression level of melanogenic proteins, including tyrosinase, TRP-1, TRP-2, and transport proteins like Rab27a, Cdc42 and Myosin Va induced by α-MSH were remarkably reversed after KL001 treatment. Mechanistically, CRY1 activation inhibited melanogenesis through CREB-dependent downregulation of MITF and CREB phosphorylation was mediated by classical cAMP/PKA pathway. In addition, the other CRY1 activator, KL044 also suppressed cAMP/PKA/CREB pathway and inhibited melanogenesis. Finally, anti-melanogenic efficacy of KL001 was confirmed by determination of melanin contents in UVB-tanning model of brown guinea pigs, which indicated that targeting CRY1 activity, via topical application of small molecule activator, can be utilized therapeutically to manage human pigmentary disorders.